The Time of Hearing Loss Onset among Workers in the Copper by-Industry and its Effective Factors - FATEMEH KHALDARI; NARGES KHANJANI; ABBAS BAHRAMPOUR; MOHAMMAD REZA GHOTBI RAVANDI; Ali ALI ASGHAR ARABI MIANROODI (International Journal of Occupational Hygiene, 2017)
Extended exposure to noise can cause permanent hearing damage. This study aimed to determine the incidence time of hearing loss and its effective factors in workers exposed to noise. This retrospective cohort study, was conducted on a total of 273 workers in various sectors of Kerman Copper by-industries Co. Their hearing status and the incidence of hearing loss (hearing threshold higher than 25 dB) were measured at regular intervals through audiographs. Survival analysis was done using the Kaplan-Meier method and Cox Regression analysis through STATA 12. The time range (from the onset of the risk to the incidence of hearing loss) was between 8 to 14 years. Systolic blood pressure alone and in interaction with years of employment was significantly related to the incidence of hearing loss at all frequencies. Initial hearing threshold and age at employment also had a significant impact on the onset time of hearing loss. The interaction between age at employment×initial hearing threshold; and years of employment×age at employment; in both low and high frequencies had a significant impact on the incidence time of hearing loss.  Despite the availability of protective equipment in this industry, hearing loss occurred in at least half of the workers after about 10 years. High systolic blood pressure, age at employment, and initial hearing thresholds probably play a role in the incidence time of hearing loss.